2010
DOI: 10.1057/gpp.2010.37
|View full text |Cite
|
Sign up to set email alerts
|

Is the Design of Bonus-Malus Systems Influenced by Insurance Maturity or National Culture? — Evidence from Asia

Abstract: Most Asian countries have adopted bonus-malus systems (BMS) in automobile insurance. We evaluate the toughness towards consumers of 16 Asian BMS and its correlation with cultural and economic variables. We use principal components analysis to define a Maturity Index of insurance markets and find supporting evidence for a conjecture that, as markets become more mature and policyholders more sophisticated, countries adopt tougher BMS. In addition, we find, using regression analysis, that using a Common Law legal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 14 publications
1
6
0
Order By: Relevance
“…This proves our hypothesis H2 true. Long term orientation positively impacts the insurance demand in our study which supports our Hypothesis 2 and also prior research done in the field by Park, Lemaire and Chua (2010). The finding can be explained by the fact that the greater a society is long term oriented higher will be the propensity of the society to invest in long term life insurance products.…”
Section: Cultural Variablessupporting
confidence: 90%
See 1 more Smart Citation
“…This proves our hypothesis H2 true. Long term orientation positively impacts the insurance demand in our study which supports our Hypothesis 2 and also prior research done in the field by Park, Lemaire and Chua (2010). The finding can be explained by the fact that the greater a society is long term oriented higher will be the propensity of the society to invest in long term life insurance products.…”
Section: Cultural Variablessupporting
confidence: 90%
“…Inclusion of cultural factors increases the predictive ability of the regression model on life insurance consumption by 13%, highly significant Chui and Kwok (2008). Significant impact of cultural variables on non-life insurance consumption was found by Lemaire (2010). Blocking and bootstrapping statistical techniques Treerattanapun (2011) was used and significant impact of cultural factors was observed on non-life insurance consumption studying 82 countries across a 10-year period.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Esho et al (2004) also investigate the impact of the legal system, but find it non-significant after controlling for income and property rights. Recently, Park et al (2010) showed that the use of a common law legal system is the most important determinant of the toughness of bonus-malus systems in automobile insurance. Therefore, a positive relationship is hypothesised with non-life insurance consumption.…”
Section: Institutional Factorsmentioning
confidence: 99%
“…Esho, Kirievsky, and Zurbruegg [2004] also investigate the impact of the legal system but find it insignificant after checking income and property rights. Recently Park, Lemaire, and Chua [2010] showed that the use of a Common Law legal system is the most important determinant of toughness of bonus-malus systems in automobile insurance. Therefore it is hypothesized that there is a positive relationship with nonlife insurance consumption.…”
Section: Institutional Factorsmentioning
confidence: 99%